Ru nanoparticles supported on alginate-derived graphene as hybrid electrodes for the hydrogen evolution reaction. (2nd December 2021) - Mallón, Laura; Cerezo-Navarrete, Christian; Romero, Nuria; Puche, Marta; García-Antón, Jordi; Bofill, Roger; Philippot, Karine; Martínez-Prieto, Luis M.; Sala, Xavier
Abstract : Ultra-small Ru NPs grown on biomass-derived bare/P-doped graphene supports yield efficient and durable electrocatalytic H2 production from water. Abstract : The development of organic–inorganic hybrid materials for redox catalysis is key to access new energy conversion schemes and the sustainable production of dihydrogen. Here, bare and P-doped graphene arising from the pyrolysis of biomass (alginate from marine algae) has been used as a support for the growth and stabilization of ultra-small Ru/RuO2 NPs through organometallic synthesis. P-doped graphene allows obtaining smaller and better dispersed NPs in hybrid electrodes of lower roughness and electroactive surface area. Electrochemical activation of the as-synthesised supported nanoparticles by reduction of the passivating RuO2 layer generates excellent HER electrocatalysts under acidic conditions ( η 10 of 29 mV and 15 mV for the bare and P-doped electrodes, respectively). P doping, identified as surface phosphates by 31 P solid state NMR, induces improvement of all HER benchmarking parameters studied, including overpotential and exchange and specific current densities. All studied materials show excellent long-term stability and selectivity for hydrogen generation with no sign of deactivation after 12 h under turnover conditions and almost quantitative faradaic efficiencies.